Research advance and clinical implication of circZNF609 in human diseases - Jieyi Luo; Shengchun Wang; Lu Zhang; Lu Zhang; Shanshan Wu; Weirang Zheng; Xueshan Huang; Xiaoxia Ye; Minhua Wu (Biotechnology & Biotechnological Equipment, 2022)
AbstractCircular ribonucleic acids (circRNAs) are single-stranded RNAs with covalently closed-loop structures that lack terminal 5′ caps and 3′ poly-(A) tails. Recent evidence confirmed that some circRNAs can be translated into proteins. More importantly, there is a growing body of evidence that dysregulation of circRNAs is closely associated with the development of human diseases, especially malignant tumors. CircZNF609 is a novel circular RNA with an open reading frame and an internal ribosomal entry site that can interact with microRNAs and mRNAs and be translated into proteins. Studies have shown that circZNF609 is abnormally expressed in various human diseases, especially malignant tumors such as hepatocellular carcinoma, nasopharyngeal carcinoma, colorectal cancer and glioma, which lead to the occurrence and development of diseases. This article attempts to provide a comprehensive overview of the structural properties of circZNF609 discovered so far and focuses on the pathogenesis of circZNF609 in human diseases and its potential clinical application value. Finally, we elaborate on the directions of future investigations of this molecule.